2015
DOI: 10.3109/10826084.2014.998234
|View full text |Cite
|
Sign up to set email alerts
|

Growth Models of Maternal Smoking Behavior: Individual and Contextual Factors

Abstract: Background Persistent maternal smoking during pregnancy, reduction or cessation during pregnancy, and smoking initiation or resumption postpartum impel further research to understand these behavioral patterns and opportunities for intervention. Objectives We investigated heterogeneous longitudinal patterns of smoking quantity to determine if these patterns vary across three maternal age groups, and whether the influence of individual and contextual risk factors varies by maternal age. Methods Separate gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…Results are largely consistent with the literature regarding the effect of maternal age at childbirth (Meschke et al, 2013); education (Laborde & Mair, 2012); marital status (Tsai et al, 2010); income (Jagodzinski & Fleming, 2007); employment (Mumford & Liu, 2015); postpartum depression (Munafo, Heron, & Araya, 2008); and breastfeeding (Jagodzinski & Fleming, 2007). This study adds to the literature by examining how maternal smoking and drinking fluctuate concurrently in concert with the context of demographic and behavioral correlates.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results are largely consistent with the literature regarding the effect of maternal age at childbirth (Meschke et al, 2013); education (Laborde & Mair, 2012); marital status (Tsai et al, 2010); income (Jagodzinski & Fleming, 2007); employment (Mumford & Liu, 2015); postpartum depression (Munafo, Heron, & Araya, 2008); and breastfeeding (Jagodzinski & Fleming, 2007). This study adds to the literature by examining how maternal smoking and drinking fluctuate concurrently in concert with the context of demographic and behavioral correlates.…”
Section: Discussionsupporting
confidence: 86%
“…Despite a concerning level of concurrent use during the perinatal period and shared risk factors, e.g., mental disorders (Ingersoll, Hettema, Cropsey, & Jackson, 2011), being unmarried (Tsai, et al, 2010), curtailed breastfeeding (Jagodzinski & Fleming 2007), longitudinal patterns of maternal smoking (Mumford & Liu 2015) and drinking (Liu, Mumford, & Petras, 2015) have only been modeled separately. To inform public health and clinical efforts in better allocating prevention efforts, we investigate distinct trajectories representing single and dual usage of alcohol and cigarettes by mothers from pre-conception through the early parenting years, and the extent to which mothers’ baseline characteristics are associated with these patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the African-American mothers, more of the White mothers were classified in the chronic smoker trajectory (52% vs. 32%) and fewer were in the non-smoker trajectory (29% vs. 34%), consistent with previous findings among men (White et al, 2004). In the Early Childhood Longitudinal Study (ECLS-B), White mothers were also more likely than African-American mothers to be in one of the smoking trajectories rather than in the non-smoking class, regardless of their age (Mumford & Liu, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…White et al (2004) found more African-American males in the non-smoker group, and more White males in the chronic smoker group. Similarly, there were more White mothers in the smoking trajectories and more African-American mothers in the non-smoking trajectory in the Early Childhood Longitudinal Study (ECLS-B: Mumford et al, 2014; 2015). There may also be an interaction or —crossover effect for race and age: White adolescents are more likely to smoke, but African-Americans who smoke are less likely to desist in adulthood (Evans-Polce et al, 2015; Geronimus et al, 1993; Kandel et al, 2011; Lawrence et al, 2014; Yuan, 2011).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation